Мудреці сербських народних новел - Самарджія, С. (Народна творчість та етнологія, 2012)
Old men and girls have different positions in the patriarchal community. Opposite status is both privileged (experience – ancestors; youth – fertility) and is characterized by the realities of life: their departure from the community is unavoidable (death; marriage). So, it is a mere chance that their ambivalent type of characteristic depends on oral genres, while in some novelles they are the main protagonists – bearers of the same, privileged features.